2014
DOI: 10.1590/2176-9451.19.5.116-122.oar
|View full text |Cite
|
Sign up to set email alerts
|

Determining shapes and dimensions of dental arches for the use of straight-wire arches in lingual technique

Abstract: INTRODUCTION: This study aims to determine the shape and dimension of dental arches from a lingual perspective, and determine shape and size of a straight archwire used for lingual Orthodontics. METHODS: The study sample comprised 70 Caucasian Brazilian individuals with normal occlusion and at least four of Andrew's six keys. Maxillary and mandibular dental casts were digitized (3D) and the images were analyzed by Delcam Power SHAPET 2010 software. Landmarks on the lingual surface of teeth were selected and 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 16 publications
(36 reference statements)
0
29
2
Order By: Relevance
“…In another similar study, Park et al 6 used three-dimensional virtual models for digitizing the reference points and described four clusters in the Korean population, namely wide, narrow, tapering and ovoid types. Kairalla et al 5 used linear measurement instead of polynomial equations to describe arch forms in Caucasian Brazilians. They concluded that the lingual arch form was parabolic in For personal use only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another similar study, Park et al 6 used three-dimensional virtual models for digitizing the reference points and described four clusters in the Korean population, namely wide, narrow, tapering and ovoid types. Kairalla et al 5 used linear measurement instead of polynomial equations to describe arch forms in Caucasian Brazilians. They concluded that the lingual arch form was parabolic in For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, very few studies have been done about arch form from the lingual/palatal perspective. [4][5][6] The number of patients undergoing lingual appliance therapy has grown markedly in the past few years. [7][8][9] Customization of arch wires to match the patient's arch form is an important step in labial as well as lingual orthodontics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate the dental arch form and size, previous studies have used polynomial functions 10 13 25 or linear measurements. 26 27 The current study applied polynomial functions as these follow the curvature of the arch and seem more similar to those used in the straight-wire technique. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Park et al in 2015 also provided a new classification of maxillary and mandibular lingual arch forms: Narrow, tapering and ovoid according to intercanine and intermolar widths and their best-fit curves on lingual surface of dentition. [4,5]…”
Section: Appliance Designmentioning
confidence: 99%